Soft X-ray Laser Microscopy of Lipid Rafts towards GPCR-Based Drug Discovery Using Time-Resolved FRET Spectroscopy - Tatsuhiko Kodama; Shin Yoneya; Hiroto Kuroda; Motoyoshi Baba; Kazuyuki Masuda; Takao Hamakubo; Tohru Kozasa (MDPI AG, 2011)
Many signaling molecules involved in G protein-mediated signal transduction, which are present in the lipid rafts and believed to be controlled spatially and temporally, influence the potency and efficacy of neurotransmitter receptors and transporters. This has focus interest on lipid rafts and the notion that these microdomains acts as a kind of signaling platform and thus have an important role in the expression of membrane receptor-mediated signal transduction, cancer, immune responses, neurotransmission, viral infections and various other phenomena due to specific and efficient signaling according to extracellular stimuli. However, the real structure of lipid rafts has not been observed so far due to its small size and a lack of sufficiently sophisticated observation systems. A soft X-ray microscope using a coherent soft X-ray laser in the water window region (2.3-4.4 nm) should prove to be a most powerful tool to observe the dynamic structure of lipid rafts of several tens of nanometers in size in living cells. We have developed for the X-ray microscope a new compact soft X-ray laser using strongly induced plasma high harmonic resonance. We have also developed a time-resolved highly sensitive fluorescence resonance energy transfer (FRET) system and confirmed protein-protein interactions coupled with ligands. The simultaneous use of these new tools for observation of localization of G-protein coupled receptors (GPCRs) in rafts has become an important and optimum tool system to analyze the dynamics of signal transduction through rafts as signaling platform. New technology to visualize rafts is expected to lead to the understanding of those dynamics and innovative development of drug discovery that targets GPCRs localized in lipid rafts.